"Truth" is a divine name : hitherto unpublished papers of Edward A. Synan, 1918-1997 - Synan, Edward A. (Value Inquiry Book Series, 2010)
This volume contains essays on an array of topics originally presented orally by a master teacher and scholar. With characteristic rhetorical elegance, Msgr. Synan, late professor at the Pontifical Institute in Toronto, delivered these papers in a variety of settings on issues relating to his specialty of mediaeval Christian philosophy and to his interest in Jewish-Christian dialogue, on the theology of sanctity and of death, and on morally significant historical events. Medieval figures represented here include Aquinas, Augustine, Abelard, and Godfrey of St. Victor; some topics treated are war and peace, philosophical innovations, ecclesiology, evil, goliardic verse, law and abortion, Church councils and Jews in the Middle Ages, and convictions uniting Jews and Christians. This book also contains representative sermons-including a Month's Mind for Etienne Gilson, an introduction detailing Synan's background and professional contributions, an updated bibliography of his published works, and an extensive index. Especially appealing to those who knew Synan are three posthumous tributes and thirteen photographs from throughout his life. The selections in this volume are scholarly but non-technical, intended for anyone moved to seek elucidation of the topics discussed.